SUBJECT TEST IN BANUA LANGUAGE CLAUSE CONSTRUCTIONS: A TYPOLOGICAL APPROACH - Wijiati, Iva Ani; Ilham, Muhammad; Romadhan, Achmad Dicky (Universitas Muhammadiyah Makassar, 2025)
Banua Language is one of the languages originating from the province of East Kalimantan. Banua Language is part of the Austronesian language family. This research on Banua Language uses a syntactic typology approach. The aim of this study is to explain the behavior of subjects in clause construction within Banua Language. As a regional language in East Kalimantan, Banua Language has a unique syntactic structure. Not much research has been done on the function and position of subjects in this language. Therefore, this study examines subjecthood through canonical position, relativization, and control, the three main tools according to Keenan and Comrie (1983). The distributional method was used to analyze data collected from native speakers through elicitation and uninvolved observation techniques. The study shows that in Banua Language, the subject always precedes the verb in both intransitive and transitive clauses. Additionally, the subject can be relativized exclusively using the form